Skandinavija lietuvių diplomatijoje 1915-1917 metais - Grigaravičiūtė, Sandra (Lietuvos istorijos studijos, 2000)
1914-1917 Lithuanian politics suggested the Lithuania orientation question and decided to choose - The West - during Vilnius Lithuanians’ conference on 18-22 September 1917. The Northern orientation of Lithuanians wasn’t so actual in conforming with the West orientation, but it didn’t mean that orientation to Scandinavia wasn’t fixated in Lithuanians’ political mentality. The facts in archive documents, old press, memoirs of M. Yčas, J. Tumas Vaižgantas, V. Bartuška, and the Lithuanian historians such as R. Lopata, A. Eidintas, A. Gaigalaitė. These materials obviously explore that the tradition of Lithuanians’ diplomacy in Scandinavia existed before 1918. We can define this tradition as the possibility of Lithuanian diplomacy to orientate in the political conjuncture of the First World War and their humanity, political and propaganda activity to become Lithuania independent, to orient to Scandinavian countries. When we talk about Lithuanian diplomacy in 1915-1917, we talk about Lithuanian diplomacy which is based on moral motivation, because the juridical motivation couldn’t be released, although it was possible. The choice to orient to Scandinavia depended on subjective and objective factors of the orientation of the Lithuanians. The first one - the political neutrality of the Scandinavian countries. It helped the Lithuanians to make a solution for economical and political existence. The second one - the blockade of Germany. They forbid sending information and letters abroad and back, closing the Lithuanian newspapers. The best way to break through that blockade was to find a way to send it through neutral countries: Switzerland, Denmark, Sweden, USA. The forbidding of the Russian government to send money to the territories occupied by German military force was the third objective factor which forced the Lithuanians to choose the Scandinavian orientation. The best way to send money from Russia to occupied Lithuania was found through Stockholm. The fourth one - the British blockade of Germany. The material help of USA Lithuanians, which had been coming from the USA to Europe, couldn’t get to Lithuania because it was a German territory and they wanted to protect their fund. The fifth one - the activity of German insurgence in Scandinavia—Stockholm (F. Reichenau, H. Lucius) and Copenhagen (U. Brokdorf-Rantzau), which aimed to propagate the separate movement of nations of the Russian empire. The sixth one - the policy of Polish diplomats. It was underlined in the first conference of Lithuanians in Stockholm in October 1915, where it was said about the importance of blocking the Polish propaganda of a new-type union. The seventh one - subjective factor - political activity of Lithuanians, related to the reconstitution of Lithuanian self-dependence, which became an international factor. The aims of Lithuanian diplomacy in Scandinavia had formed two concepts of Scandinavia. Humanitarian aims formed Scandinavia - bridge, and political-propaganda aims - Scandinavia - political centre of Lithuanian policy. Scandinavia became the financial and informational bridge to Lithuania when Lithuanian society started to send money and letters throughout Stockholm (Swedish-Lithuanian help committee) in Vilnius and from Vilnius to Lithuanians in foreign countries. In Stockholm, Lithuanians’ conferences took place and concentrated propaganda of Lithuania: some articles about the Lithuanians in occupied territory were written in Swedish newspapers, and lectures were arranged about Lithuanian history and parties to proclaim the will of Lithuania to be independent. That formed Stockholm as the political centre of the Lithuanian people. The orientation of Lithuanians to the Scandinavian countries at the end of 1917 became measures of Lithuanian diplomacy, which tried to internationalise the Lithuania question and grant juridical ground to Lithuanian diplomacy, which represented the Lithuanian nation. Scandinavia in 1917 meant to Lithuania the possibility to choose between the West-East and North-South geopolitical axis, and the orientation of Lithuania to Scandinavia could be interpreted in two ways: to Germany as orientation to Germany, and to Great Britain - as orientation to Scandinavia and the states of the Entente.